2010
DOI: 10.1007/s10597-010-9293-5
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Adolescent Satisfaction with Mental Health Services: Does it Relate to Youth Diagnosis, Age, Gender, or Treatment Outcome?

Abstract: Consumer satisfaction with treatment is important information for providers of mental health services. The goal of the current study was to examine the relationship between youth and parent satisfaction ratings and the following youth variables: gender, age, primary diagnosis, and changes in functioning and symptomatology after 6 months of services. Results demonstrated that in a large sample of youth receiving community mental health services satisfaction with services differed as a function of the adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
42
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 24 publications
12
42
2
Order By: Relevance
“…This is consistent with the finding from several other studies that found a weak-to-moderate correlation between these respondents (Garland et al, 2007; Lambert et al, 1998; Stüntzner-Gibson et al, 1995; Turchik, Karpenko, Ogles, Demireva & Probst, 2010). Total score and comprehensive item analysis for the youth and caregiver SSS are found in table 1.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the finding from several other studies that found a weak-to-moderate correlation between these respondents (Garland et al, 2007; Lambert et al, 1998; Stüntzner-Gibson et al, 1995; Turchik, Karpenko, Ogles, Demireva & Probst, 2010). Total score and comprehensive item analysis for the youth and caregiver SSS are found in table 1.…”
Section: Resultssupporting
confidence: 93%
“…To the best of our knowledge, this is the first study to assess quality of care from foster parents' perspective and associations with youth, placement and service characteristics. Overall, the foster parents reported positive service experiences, which is in line with findings in the general population that most parents were satisfied with health services provided for their children (Aarons et al, 2010; Bjertnaes et al, 2008; Garland et al, 2007; Turchik et al, 2010). A large majority of foster parents reported that clinicians communicated in a way that was easy to understand and that they had confidence in the clinicians' professional skills.…”
Section: Discussionsupporting
confidence: 81%
“…Currently, there is a lack of research on characteristics related to foster parents' experiences of service quality following contact for the youths in their care. Studies of the general population have indicated that younger age (Bjørngaard, Wessel Andersson, Osborg Ose, & Hanssen‐Bauer, 2008; Holmboe, Iversen, & Hanssen‐Bauer, 2011; Turchik, Karpenko, Ogles, Demireva, & Probst, 2010), shorter waiting time (Bjørngaard et al, 2008; Holmboe et al, 2011), more treatment sessions and longer treatment episodes (Bjørngaard et al, 2008; Garland, Haine, & Lewczyk Boxmeyer, 2007; Holmboe et al, 2011) were associated with positive parent experiences with child and adolescent mental health services (CAMHS). However, these results were equivocal, and many of the effects identified were weak.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the plethora of research on treatment satisfaction among clients of substance abuse treatment programs (Carlson and Gabriel 2001; Perreault et al 2010), family support programs (Herman 1997), and inpatient (Holcomb et al 1998; Howard et al 2003; Minsky et al 1995) and outpatient psychiatric services (Berghofer et al 2010; Cho and Kim 2012; Edlund et al 2003; Garland et al 2003; Leavey et al 1997; Perreault et al 1993, 2001; Turchik et al 2010), to our knowledge no research has examined the relationship between treatment satisfaction and subjective measures of improvement among clients of pathological gambling treatment programs. Outcome research on problem gambling treatment itself is quite limited (Lesieur and Rosenthal 1991; Sylvain et al 1997; Walker 1993).…”
Section: Introductionmentioning
confidence: 99%